Colec12 and Trail signaling confine cranial neural crest cell trajectories and promote collective cell migration. Issue 5 (6th February 2023) - McLennan, Rebecca; Giniunaite, Rasa; Hildebrand, Katie; Teddy, Jessica M.; Kasemeier‐Kulesa, Jennifer C.; Bolanos, Lizbeth; Baker, Ruth E.; Maini, Philip K.; Kulesa, Paul M.
Abstract: Background: Collective and discrete neural crest cell (NCC) migratory streams are crucial to vertebrate head patterning. However, the factors that confine NCC trajectories and promote collective cell migration remain unclear. Results: Computational simulations predicted that confinement is required only along the initial one‐third of the cranial NCC migratory pathway. This guided our study of Colec12 (Collectin‐12, a transmembrane scavenger receptor C‐type lectin) and Trail (tumor necrosis factor‐related apoptosis‐inducing ligand, CD253) which we show expressed in chick cranial NCC‐free zones. NCC trajectories are confined by Colec12 or Trail protein stripes in vitro and show significant and distinct changes in cell morphology and dynamic migratory characteristics when cocultured with either protein. Gain‐ or loss‐of‐function of either factor or in combination enhanced NCC confinement or diverted cell trajectories as observed in vivo with three‐dimensional confocal microscopy, respectively, resulting in disrupted collective migration. Conclusions: These data provide evidence for Colec12 and Trail as novel NCC microenvironmental factors playing a role to confine cranial NCC trajectories and promote collective cell migration. Key Findings: Model simulations predict neural crest cell confinement along the entire length of the migratory domain is not required to maintain discrete streams over long distances. Colec12 and Trail, we previously identified, confine neural crest cell trajectories off of protein stripes in in vitro stripe assays. Gain‐ or loss‐of‐function of any single factor or in combinations significantly disrupt the in vivo cranial neural crest migratory pattern.